Answer:
-2n +6
Explanation:
The expression we are given is:
5n + 6 + (-7n)
We want to combine like terms. First, let's analyze each term.
5n ⇒ has a variable, "n"
5 ⇒ does not have a variable
-7n ⇒ also has a variable, "n"
The like terms in this case are 5n and -7n, since they both include a variable. Let's combine the like terms.
5n + 6 + (-7n)
(5n - 7n) +6
Subtract 7n from 5n.
(5-7) *n +6
(-2)*n +6
(-2n)+6
-2n + 6
There are no more like terms, so this is simplified as much as possible.
The expression 5n+6+(-7n) after combining the like terms is -2n+6.